Acantholytic dyskeratotic epidermal nevus: case report. - Garofalo, L.; Mazzotta, F.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
A case of acantholytic dyskeratotic epidermal nevus is reported in a 27-year-old woman. The Authors stress the importance of pathological examination for the classification of epidermal nevi and the relevant genetic counseling.